Patterns of controversy and consensus in German, Canadian, and US online news on climate change. (January 2020) - Tschötschel, Robin; Schuck, Andreas; Wonneberger, Anke
Graphical abstract: Highlights: German media focus on controversies about efficacy and portray a wide range of actors. Canadian media emphasise consensus to limit emissions, but rarely discuss efficacy. US media foreground political divisions concerning the need for policy to limit emissions. Rare portrayals of controversy about climate science are driven by US politicians. Media seem to index seemingly relevant positions across countries, with variation in emphasis. Abstract: Individual action and support for policy to tackle climate change have been linked to perceptions of political and scientific controversy and consensus concerning the issue. Recent media effects research indicates that presentation of agreement or conflict between actors' opinions influences how audiences respond to news about climate change and policy. While some national case studies have investigated portrayals of actors' positions on important questions regarding climate change in the media, they are largely absent from comparative research. This study addresses this gap by analysing portrayals of actor-issue-positions and the emerging patterns of controversy and consensus in German, Canadian, and US coverage. Studying a sample of occurrences of climate change-related issues (N = 902) in-depth, the results show German media present political consensus about the need to limit emissions and societal controversy about the efficacy of specific mitigation measures. Presenting mainly consensus, Canadian media report more on climate change's impact, leaving aside the issue of efficacy. In the US, media emphasise political controversy — about the need to limit emissions and occasionally about climate change's impact on humans. The findings, consistent with other recent publications, can best be explained by journalists selectively indexing of seemingly relevant actor-issue-positions.